PROBLEMS OF STUDYING BYRON'S INFLUENCE ON PUSHKIN'S WORKS - Khamrayeva Dilafruz Juraevna, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
This article deals with the influence of Byron's work on the poetry of the great classic of Russian literature A.S. Pushkin.